How medical students learn in primary care. (24th October 2018) - Davis, Katherine; Doole, Emily; Cheek, Colleen; Shires, Lizzi
Summary: Background: General practice placements are important in medical education, but little is known about positive student experiences. Methods: Focus group interviews were conducted with medical students. Interview transcripts were analysed thematically and incorporated into an overarching conceptual framework. Results: Of the 22 eligible students, 21 students participated. Students viewed positively placements where they felt part of the team, had the opportunity to practise procedural skills, learned at a level congruent to their stage and gained experience practising independently. Students were not motivated when they did not feel valued, or where learning opportunities were inconsistent with personal learning objectives. Discussion: Self‐determination theory (SDT) proposes that when people perceive that they have more control over their learning, a sense of competence in the activities and tasks required of them, and a sense of being cared for and connected with another, they will be more likely to integrate learning and behaviour change. Conclusion: Strategies to support medical student learning in general practice are provided. Situated within the SDT framework, these findings may assist others to adopt the strategies most likely to enhance student motivation to learn. Students identified developing independence and decision‐making with graduated supervision as a positive experience